Penyuluhan Pengenalan Bahaya Kanker Payudara: Counseling on the Introduction to the Dangers of Breast Cancer - Pratiwi, Liliek; Nawangsari, Harnanik; Liswanti, Yane; Fitriani, Henny (Chakra Brahmanda Lentera Institute, 2023)
According to Globocan data for 2020, breast cancer has reached 68,858 cases out of a total of 396,914 new cases in Indonesia. Unfortunately, about 70% of cases are detected too late and are at an advanced stage. The impact for Indonesia is of course in addition to being a double burden economically but also the degree of public health. Currently found cases of breast cancer suffered by adolescents, even 14 years old. Therefore the need for pro-active academic efforts to help reduce breast cancer cases. One way is through health promotion by counseling the introduction of the dangers of breast cancer to adolescents. Counseling methods in groups of youth and online. Adolescent counseling participants with a population of 35 people. The media used PowerPoint and Google meet, which lasted approximately 50 minutes. As a result of community service, it appears that 50% of adolescents can answer questions about breast cancer. As well as the enthusiasm of teenagers in asking in detail. Teenagers participating in online counseling can understand and increase their knowledgeabout the dangers of breast cancer. Counseling can be done at a later time, so that youth can become Change Agents.